Exploitative abuse and abuse of economic dependence: What can we learn from the industrial organization approach? - Patrice Bougette; Oliver Budzinski; Frédéric Marty (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2017)
This article aims to provide a detailed analysis of the concept of economic dependence and exploitative abuse through their evolution in competition law and economics and in European case law. First, while the theoretical roots of these concepts may be found in economic theory, we show that the issue has long been ignored or only reluctantly considered in competition law enforcement, mainly because of a lack of available and reliable economic criteria. Second, although its primary objective was to measure market power in an oligopoly context, we examine how current empirical industrial organization methodology allows a sophisticated measure of the economic dependence among suppliers and distributors. Third, we discuss the possibility of relying on the industrial organization approach to address these issues.
Keywords: K21; L12; L40; L42; 330; exploitative abuse; abuse of economic dependence; competition law; European Commission; effects-based approach